Acute Oral Toxicity Study of Povidone-Iodine in Wistar Rats Using Up-and-Down Procedure - salihu, Sabo Isa; Abubakar, Zainab Salihu; Waziri, Ali; Suleiman, Nuhu; Mary Olowome, Oluwakemi; Abdulsalam, Hassan; Sani, Dahiru; Mamman, Mohammed (Sahel Journal of Life Sciences FUDMA, 2024)
This study was conducted to assess the acute oral toxicity of Povidone iodine in Wistar rats and determine its safety profile. The up and down method as per Organization for Economic Co-operation and Development guidelines using 15 adult male Wistar rats. They were randomly divided into three groups, given varying amounts of distilled water, 2000 and 5000 mg/kg to determine the median lethal dose (LD50). Clinical signs and mortality were observed for 48 hours and 14 days for immediate and delayed toxicity. Blood samples were collected at the end of the experiment for haematological and serum biochemical analysis for kidney and liver functions. Also, the kidney and liver were harvested, preserved, and processed for histomorphological evaluation. The result from this study indicates that Mortality (60 %) was observed in the group administered with 5000 mg/kg of PV-I within 3 h of administration. In contrast, the group served with 2000 mg/kg of PV-I, and the control remained viable up to 14 d of the experiment, the median lethal (LD50) dose of PV-I is less than 5000 mg/kg in Wistar rats. No significant (P> 0.05) difference was observed in the haematological parameters and serum biochemical markers for the kidney and liver function tests between the treatment and the control group. Furthermore, a histomorphological examination of the kidneys and liver shows normal kidneys with slight hepatic necrosis in the group administered with 2000 mg/ kg BW of PV-I. In conclusion, PV-I is safe for Wistar rats in doses below 2000 mg/kg.